Fluorescence visualization directly monitors microphase separation behavior of shape memory polyurethanes. (June 2021) - Liu, Juan; Chen, Zhigang; Hu, Chengshen; Yang, Wei; Wang, Jinfeng; Xu, Weilong; Wang, Yuanliang; Ruan, Changshun; Luo, Yanfeng
Highlights: A novel inherent fluorescent shape memory polyurethane is successfully designed and prepared for the first time. Microphase separation of shape memory polyurethane can be monitored by fluorescent visualization in a direct, fast and nondestructive manner. The mechanism for phase separation is further clarified by semi-quantitative calculation from fluorescence visualization images. Abstract: Shape memory polyurethanes (SMPUs) with excellent shape memory effects (SMEs) can be served as a kind of smart materials capable of responding to external stimuli. Microphase separation behavior between soft and hard segments of SMPUs is recognized as structural basis and an intrinsic factor for SMEs of SMPUs. Therefore, effective detection of microphase separation behavior is highly desired in order to clarify the mechanism of SMEs and further regulate the SMEs of SMPUs. Although great progresses have been made in detection of microphase separation behavior of SMPUs, non-destruction and real-time visualization for tracking the microphase separation behavior during the shape memory process of SMPUs remains a great challenge. Herein, a facile fluorescence visualization method is presented to directly, fast and nondestructively monitor the microphase separation behavior of SMPUs. Specifically, a series of novel inherent fluorescent SMPUs (IFPUs) with different hard segment contents (10%, 15% and 20%) were first prepared by using a fluorescent small molecule as part of their hard segments. It was found that this fluorescent molecule could visualize the aggregation of hard segments and the corresponding microphase separation behavior in a real-time manner. Moreover, by conducting a semi-quantitative calculation of the collected fluorescent images, the size, aspect ratio and orientation of the hard segment domains could be obtained. The results indicated that increasing the contents of hard segments could enhance the microphase separation and both stretching (50%, 100% and 200%) and subsequent recovering processes could promote the formation of larger and longer hard segment domains tending to take a perpendicular orientation to stretching. Graphical abstract: Image, graphical abstract